2020
DOI: 10.18087/cardio.2020.5.n859
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and systemic inflammation in patients with chronic heart failure

Abstract: Aim To study the interrelationship between intensity of chronic systemic inflammation (CSI) with severity of the condition and intestinal microbiocenosis parameters in patients with chronic heart failure (CHF).Material and methods 47 hospitalized patients with symptomatic CHF were evaluated. The following parameters were determined: clinical condition; N-terminal pro-B-type natriuretic peptide (NT-proBNP). C-reactive protein (CRP); serum interleukins (IL) 6 and 10; and intestinal microbiocenosis composition by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…A study by Vlasov et al may confirm this. They observed that patients with chronic HF had lower levels of Ruminococcus-specific fatty acids than the control group [41].…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…A study by Vlasov et al may confirm this. They observed that patients with chronic HF had lower levels of Ruminococcus-specific fatty acids than the control group [41].…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…In addition, CD40L, monocyte chemoattractant protein‐1 (MCP‐1), adhesion molecules, myeloperoxidase and various interleukins have been studied for this purpose in addition to CRP in recent years, but no significant predictive value has been determined 4 . However, recent studies indicate the potential role of inflammation and oxidative stress and the causative agents in this disease 5 . Recent studies have shown that serum levels of soluble tumor necrosis factor‐like weak inducer of apoptosis (sTWEAK) and its receptor, cluster of differentiation 163 (CD163), may act as a cardiovascular biomarker along with other biomarkers involved in the progression of inflammation that have not been potentially studied 6 and sTWEAK have been shown to be reduced in inflammatory diseases such as HF which is associated with higher clinical complications in patients 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…4 However, recent studies indicate the potential role of inflammation and oxidative stress and the causative agents in this disease. 5 Recent studies have shown that serum levels of soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) and its receptor, cluster of differentiation 163 (CD163), may act as a cardiovascular biomarker along with other biomarkers involved in the progression of inflammation that have not been potentially studied 6 and sTWEAK have been shown to be reduced in inflammatory diseases such as HF which is associated with higher clinical complications in patients. 7,8 TWEAK is a member of the TNF superfamily and controls many cellular functions through its receptor fibroblast growth factorinducible 14 (Fn14).…”
Section: Introductionmentioning
confidence: 99%
“…Infl ammation is a common pathological process underlying diseases of infectious and non-infectious etiology, and is also one of the main regulatory mechanisms maintaining homeostasis; however, disturbance of regulation in some cases causes infl ammation to become chronic, acquiring a damaging character. The mechanisms of infl ammation are realized through the development of a systemic infl ammatory reaction, the main initiating mechanism of which is deliv-ery of cytokines and various other infl ammatory mediators into the bloodstream, leading to activation of the complement and hemostasis systems, leukocytes, microcirculatory disorders, and the development of destructive changes at lesion sites [1,2].…”
mentioning
confidence: 99%